The Correlation between Various Types of Antihypertensive Drugs and the Incidence of Acute Stroke - Athiyya Salma Hamida; Tri Wahyuliati (Universitas Muhammadiyah Yogyakarta, 2023)
Stroke is the second leading cause of death and the third leading cause of disability, whose incidence increase with hypertension. Various antihypertensives are used as secondary therapy for stroke. However, the effectiveness of each drug is still debated. This study aims to determine the correlation between various types of antihypertensive drugs on the incidence of acute stroke. This research is a cross-sectional study. Inclusion criteria included hypertensive patients who had used antihypertensive drugs for at least a year and were aged 36. We included 78 subjects, 47 men and 31 women. The drugs were ACEI + CCB (13), ARB (8), ARB + CCB (22), and CCB (35). The subject had an ischemic stroke (8) and a hemorrhagic stroke (1). The logistic regression test showed ACEI + CCB as a reference category. The result consecutively showed ARB (OR, 4.95; CI, 0.72 to 33.89; p = 0.103), CCB (OR, 2.61; CI, 0.39 to 17.01; p = 0.317), and ARB + CCB (OR, 2.36; CI, 0.19 to 29.75; p = 0.507). The antihypertensive drugs had no significant correlation with the incidence of acute stroke. It indicated that stroke risk was not triggered by antihypertensive and could effectively control hypertension and protect patients against stroke